2014
DOI: 10.1111/ejn.12785
|View full text |Cite
|
Sign up to set email alerts
|

Caged compounds for multichromic optical interrogation of neural systems

Abstract: Caged compounds have widely used by neurophysiologists to study many aspects of cellular signaling in glia and neurons. Biologically inert before irradiation, they can be loaded into cells via patch pipette or topically applied in situ to a defined concentration, photolysis releases the caged compound in a very rapid and spatially defined way. Since caged compounds are exogenous optical probes, they include not only natural products such neurotransmitters, calcium and IP3, but non-natural products such as fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 120 publications
(192 reference statements)
2
70
0
2
Order By: Relevance
“…Subsequently several chromophores have been used for uncaging of biological signaling molecules with blue light 1621 . Photochemical protecting groups sensitive to green light have also been reported 2224 , but to our knowledge no biological studies have appeared with these probes.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently several chromophores have been used for uncaging of biological signaling molecules with blue light 1621 . Photochemical protecting groups sensitive to green light have also been reported 2224 , but to our knowledge no biological studies have appeared with these probes.…”
Section: Introductionmentioning
confidence: 99%
“…Since we have shown that DEAC450 uncaging is highly wavelength-selective for 2P excitation at 900 nm [27] , our data suggest the cloaked caged neurotransmitter G5-DEAC450-GABA could be very useful for chromatically selective, two-color optoneurobiology.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 75%
“…Prior irradiation of the apical dendrite with 900nm (3 × 3 ms, 50 mW) elicited pronounced hyperpolarization, which blocked the action potential, which was restored when only short wavelength irradiation was used ( Figure 5). Since we have shown that DEAC450 uncaging is highly wavelength-selective for 2P excitation at 900 nm [27] , our data suggest the cloaked caged neurotransmitter G5-DEAC450-GABA could be very useful for chromatically selective, two-color optoneurobiology.Certainly it is the first example of a caged GABA compound that is highly active to 2P …”
mentioning
confidence: 75%
“…The γ-thiophosphate group impedes (Malmsjö et al, 2003), but does not completely prevent its enzymatic hydrolysis. A caged form of ATP 69 , which regenerates ATP upon irradiation has been studied and is potentially useful for studies of P2Rs (Amatrudo et al ., 2015). Similarly, the 1-(3,4-dimethyloxy-6-nitro-phenyl)ethyl (DMNPE) group was used to block the β-phosphate of agonist 65 to abolish its activity at the P2Y 1 R and P2Y 12 R, and this activity could be recovered upon irradiation (Gao et al ., 2008).…”
Section: P2yr Modulatorsmentioning
confidence: 99%